2016
DOI: 10.1097/j.pain.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular calcitonin gene-related peptide in spinal cord mechanisms of cancer-induced bone pain

Abstract: Severe pain is a common and debilitating complication of metastatic bone cancer. Current analgesics provide insufficient pain relief and often lead to significant adverse effects. In models of cancer-induced bone pain, pathological sprouting of sensory fibers at the tumor-bone interface occurs concomitantly with reactive astrocytosis in the dorsal horn of the spinal cord. We observed that calcitonin gene-related peptide (CGRP)-fiber sprouting in the bone was associated with an increase in CGRP content in senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…This finding provides evidence that blocking the CGRP receptor within the spinal cord is sufficient to suppress the initiation and maintenance of peripheral sensitization of trigeminal nociceptive neurons. Our result is in agreement with other studies that reported intrathecal administration of a CGRP receptor antagonist can block mechanically evoked nocifensive responses in tissues innervated by dorsal root ganglion sensory neurons (Sun et al, 2004, Adwanikar et al, 2007, Tzabazis et al, 2007, Hansen et al, 2016). Following binding of CGRP to its G-protein-coupled receptor, there is an increase in adenylate cyclase activity within those cells leading to an increase in the intracellular level of the secondary messenger cAMP (Brain and Cox, 2006).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding provides evidence that blocking the CGRP receptor within the spinal cord is sufficient to suppress the initiation and maintenance of peripheral sensitization of trigeminal nociceptive neurons. Our result is in agreement with other studies that reported intrathecal administration of a CGRP receptor antagonist can block mechanically evoked nocifensive responses in tissues innervated by dorsal root ganglion sensory neurons (Sun et al, 2004, Adwanikar et al, 2007, Tzabazis et al, 2007, Hansen et al, 2016). Following binding of CGRP to its G-protein-coupled receptor, there is an increase in adenylate cyclase activity within those cells leading to an increase in the intracellular level of the secondary messenger cAMP (Brain and Cox, 2006).…”
Section: Discussionsupporting
confidence: 94%
“…The physiological and cellular effects of CGRP are mediated via activation of the CGRP receptor, which is expressed on primary trigeminal neurons that synapse in the outer lamina of the spinal cord and the associated glial cells, astrocytes, and microglia (Wang et al, 2010, Hansen et al, 2016). To demonstrate the specificity of the CGRP-mediated response, we co-administered CGRP with the truncated CGRP molecule (CGRP 8-37 ), which acts as a competitive inhibitor of the CGRP receptor (Chiba et al, 1989, Edvinsson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have reported the morphology and molecular phenotype of spinal afferent endings in bone under normal, physiological conditions (i.e., in naive mice). Recent studies have shown an increase in density and sensitivity of sensory nerve endings in the marrow cavity and subchondral bone in response to a number of different disease states, including bone cancer (Hansen, Vacca, Pitcher, Clark, & Malcangio, ), fractures (Chartier et al, ), and osteoarthritis (Ghilardi et al, ; Zhu et al, ). How distinct populations of anterogradely labeled spinal afferent nerve endings innervating bone change in response to pathology remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…We can only speculate on this finding. In contrast, the role of neuropeptides in the transmission of nociceptive signals in the dorsal horn of the spinal cord is undisputed (Hansen et al, 2016). The 1 Hz stimulation is qualitatively not different from the 4 Hz stimulation, but 4 Hz generate a higher action potential frequency.…”
Section: Hpt (°C)mentioning
confidence: 95%
“…However, in healthy humans, cutaneous CGRP neither causes pain (Weidner et al, 2000) nor heat sensitization in the flare area (Ali et al, 1996). In contrast, the role of neuropeptides in the transmission of nociceptive signals in the dorsal horn of the spinal cord is undisputed (Hansen et al, 2016). Although there is still no direct evidence for BoNT/A to be transported axonally to the spinal endings of peripheral nociceptors in humans, there is evidence for bidirectional axonal transport in peripheral afferent fibers of the rat (Akaike et al, 2013;Papagiannopoulou et al, 2016).…”
Section: Hpt (°C)mentioning
confidence: 99%